Orthopedic and orthodontic treatment in a class II division 1 malocclusion for thumb sucking habit - Calderón Bohórquez, Carlos (2018)
In the treatment of a malocclusion class II division 1 to designate a specific treatment we have to take notice the age of the patient to consider a redirection of the maxilar complex also the use of appliances for nocive habits like thumb sucking. In this paper presents the case of a 9-year-old patient, with malocclusion II division 1, treated with headgear and a palatal crib.. Skeletal, facial and dental changes were observed.